1997
DOI: 10.1111/j.1469-8986.1997.tb02408.x
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep eye movement counts correlate with visual imagery in dreaming: A pilot study

Abstract: Based on the findings of our previously published positron emission tomography study, we proposed that recorded eye movements during REM sleep are visually targeted saccades. In the present study, we examined the correlation between the number of eye movements in REM sleep (EM) and visual imagery in dreaming (V) and provided further support for our proposal. All the observations (N = 11) were made with one individual to eliminate interindividual variation and were made during the second REM sleep period to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…The activated areas temporally related to REMs in the present study include these two neural substrates. In fact, electrical stimulation of the amygdala, hippocampus and cingulate gyrus in humans induces not elementary sensations, but sensations of dreaming and hallucination (Halgren et al 1978), and there is strong correlation between the number of REMs and visual imagery in dreaming (Hong et al 1997). These Wndings are also consistent with the notion that the activation of V1 and the subsequent activation of the amygdala and PHG reXect neural activities for generating and maintaining vivid and complex dream scenes.…”
Section: Activation Accompanying Remsupporting
confidence: 77%
See 1 more Smart Citation
“…The activated areas temporally related to REMs in the present study include these two neural substrates. In fact, electrical stimulation of the amygdala, hippocampus and cingulate gyrus in humans induces not elementary sensations, but sensations of dreaming and hallucination (Halgren et al 1978), and there is strong correlation between the number of REMs and visual imagery in dreaming (Hong et al 1997). These Wndings are also consistent with the notion that the activation of V1 and the subsequent activation of the amygdala and PHG reXect neural activities for generating and maintaining vivid and complex dream scenes.…”
Section: Activation Accompanying Remsupporting
confidence: 77%
“…Several studies report that visual imagery shares many of the functional properties and cortical structures, especially V1, used in visual perception (Kosslyn et al 1999;Klein et al 2000). When taken together with Wndings of a high correlation between the number of REMs and visual imagery in dreaming (Hong et al 1997), and that eye movements during visual imagery are not random but reXect the content of the visualized scene (Brandt and Stark 1997;Laeng and Teodorescu 2002), the activation of V1 before REM onset suggests that dream imagery, probably driven by PGO waves, occurs before REM and that REM may occur in order to scan the dream imagery. Furthermore, as shown in Fig.…”
Section: Activation Preceding Remmentioning
confidence: 99%
“…Consciousness has been suggested to be a dreaming awake state (Llinas and Pare, 1991). It has been suggested that brain sensory perceptions and imagery during dreaming may be generated and regulated by similar regions to those displaying FC changes in our study (Halgren et al, 1978;Hong et al, 1997;Kreiman et al, 2000).…”
Section: Discussionmentioning
confidence: 50%
“…REM sleep duration is also higher in long sleepers in comparison to short sleepers, the former being characterized by higher emotional sensitivity and predisposition to anxiety, sub-clinical depression and reactions of surrender (Hartmann, 1973). In healthy subjects, eye movement (EM) density in REM sleep correlates with the active participation of dreamer in his dream scenario (Rotenberg, 1988) and with visual imagery in dreaming (Hong et al, 1997). Thus, EM density in healthy subjects may correspond to the search activity in dreams.…”
Section: Rem Sleep and Dreams: Restoration Of Search Activitymentioning
confidence: 99%
“…Patients and healthy subjects display different correlations between dream mentation and physiological variables in REM sleep. In healthy subjects eye movement (EM) activity display a regular increase from the first to the last REM sleep period and its density correlates with dream content (Hong et al, 1997), in particular with subject's active participation in his own dreams (Rotenberg, 1988). It is possible to suggest that in healthy subjects EM density is a sign of search activity in dreams that normally increases from cycle to cycle.…”
Section: Functionally Sufficient Vs Function-ally Insufficient Rem Smentioning
confidence: 99%